Knowledge, attitude, and utilization of drugs toward COVID-19 pandemic among Bale Zone residents, Southeast Ethiopia. (July 2021) - Mamo, Ayele; Hassen, Mesud M; Adem, Ahmednur; Teferu, Zinash; Kumbi, Musa; Husen, Abduljewad; Solomon, Damtew; Lette, Abate; Hailu, Sintayew; Sinba, Edao; Abduletif, Abdushakur M; Kassim, Jeylan; et al.
Background: Coronavirus disease is a highly transmittable and pathogenic viral infection caused by severe acute respiratory syndrome coronavirus 2, which poses therapeutic dilemmas. Some suggestions for drug treatment seem problematic. Beliefs about the causes of health problems are determinants of treatment seeking decisions. Hence, one of the alternatives for the solution of health problems is employing traditional medicine to prevent coronavirus disease 19. Objective: To assess the knowledge, attitude, and utilization of drugs toward the coronavirus disease 19 pandemic among Bale zone residents. Methods: Community-based cross-sectional study was conducted among the Bale Zone population from May 30 to June 30, 2020. Eight hundred fifty-four participants were selected using a single population formula, and a multistage sampling technique was employed. Data were analyzed using SPSS version 25.0. Descriptive and binary logistic regression was used to analyze the outcomes. A p value ⩽ 0.05 was considered statistically significant. Results: Out of the total 854 respondents, about 534 (62.5%) got information about coronavirus disease 19 from TV/radio. More than two-thirds (71.9%) of the respondents have known that severe acute respiratory syndrome coronavirus 2 has no curative drugs, and 65.4% had a more appropriate attitude toward overall drug use in coronavirus disease 19. Level of education and, attitude towards drug use were singnificantly associated with knowledge of drugs, source of information about coronavirus disease 19 and having good practice were significantly associated with atittude toward drug utilization. Conclusion: One out of two study participants have good knowledge regarding drugs to the coronavirus disease 19 pandemic. Illiterate people in the community were identified to have poor knowledge about drugs, hence community educuation program is important to improve the knowledge about drugs towards the coronavirus disease 19 pandemic.